2013
DOI: 10.1371/journal.pone.0080378
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Functionality of Electronic Prescribing Systems in English Acute NHS Trusts: A Cross-Sectional Survey

Abstract: ObjectivesTo describe current use of electronic prescribing (EP) in English acute NHS hospital trusts, and the use of multiple EP systems within the same hospital.DesignDescriptive cross-sectional postal survey.SettingAcute NHS hospital trusts in England.ParticipantsThe survey was sent to chief pharmacists in all acute English NHS hospital trusts in 2011. Where trusts comprised multiple hospitals, respondents were asked to complete the questionnaire for their main acute hospital.Main Outcome MeasuresPrevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 12 publications
0
45
0
1
Order By: Relevance
“…29 The response data suggest an unmet need for AMS-relevant features such as recording of indication and "soft stop" functionality;…”
Section: Discussionmentioning
confidence: 99%
“…29 The response data suggest an unmet need for AMS-relevant features such as recording of indication and "soft stop" functionality;…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, several attempts have been made to implement HEPMA systems in secondary care. In 2013 only 13% of hospitals had hospitalwide HEPMA systems (Ahmed et al 2013). This is however expected to rise rapidly as a result of the £500 Million Safer Hospitals Safer Wards technology fund launched in 2013 and a policy target of complete implementation across the NHS by 2020 (Carter 2015).…”
Section: The Uk Context For Hospital Electronic Infrastructuresmentioning
confidence: 99%
“…Before extensive implementation of IT systems at pediatric institutions in the USA, it was suggested that 93 % of medication errors could have been prevented by IT such as computerized provider order entry (CPOE) and computerized clinical decision support (CDS) [5]. Implementation of CPOE and CDS have thus increased over the last decade worldwide [8,9]. Overall, these systems appear to have decreased prescribing errors in the pediatric population, but results have been variable and outcomes related to these systems are likely dependent on the implementation strategy [10,11].…”
Section: Introductionmentioning
confidence: 99%